Planejamento, síntese e avaliação farmacológica de compostos híbridos potencialmente ativos para o tratamento da anemia falciforme - Santos, Jean Leandro dos [UNESP] (2007)
The sickle cell disease is a chronicle hereditary hemolitic anemia due to the inheritance of each one of the ancestors, to a gene for the hemoglobina S. It is characterized for the red globule presence that, when private of oxygen, they take the form of a scythe. It has been reported that patient with sickle cell disease present increase the circulating levels of cytokines, including TNF-alpha. The hydroxyurea (HU), a cytotoxic drug, is the mainly available therapeutical strategy for the treatment which acts as nitric oxide source benefiting patient for increasing the levels of fetal hemoglobin (HbF), a kind of hemoglobin that decrease the polimerizaron of hemoglobin S in deoxy state. In this context, inside of a research program that aims at the designing, synthesis and pharmacological evaluation of new drug candidates we synthetized a hybrid compounds series with properties of TNF-alpha inhibition and nitric oxide donors, acting by a sinergic effect that may improve the life quality of sickle cells patients. We had sinthetized six compounds: five nitrates and one sulfonamidic.The compounds : 1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)methyl nitrate (compound I); (1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)ethyl nitrate (compound II); 3-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)benzyl nitrate (compound III); 4-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)-N-hydroxybenzenesulfonamide (compound IV); 4-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)benzyl nitrate (compound V); 2-[4-(1,3-dioxo-1,3-dihydro-2H-isoindol-2-yl)phenyl]ethyl nitrate (compound VI), had been synthetized using linear synthetic methodology, with good global yields. All compounds had presented antiinflamatory activity, and white blood cells infiltration inhibition properties. Aryl compounds III, IV and V had presented minor mutagenic effect when comparative to compounds I, II and VI. Compounds IV and VI, showed activity in the assay with erythroid progenitor K562 cells, increasing the genic expr